A CONTRIBUIÇÃO DE UM DICIONÁRIO HISTÓRICO: O DICIONÁRIO HISTÓRICO DO PORTUGUÊS DO BRASIL - Murakawa, Clotilde (Organon, 2011)
This article presents the theoretical and methodological road used to construct theHistorical Dictionary of Brazilian Portuguese in the XVI, XVII and XVIII centuries (sponsoredby CNPq). Starting with some examples and models of historical and diachronic dictionaries weset the model that structures the Dictionary; it has the purpose of assembling in a single bookthe Portuguese language lexicon responsible for the construction of the Portuguese language inBrazil. Our reference basis is a data bank with many sorts of sources existing along the threecenturies of the Brazilian colonial history. This data bank provides the nomenclature of thehistorical dictionary and allows the construction of the lexicographical definition through itslexical context that is followed by consecrated examples. This article also presents thecontributions of the dictionary to future studies of the Brazilian Portuguese.